Chasing Your Tale: On Working Title and the Creative Journey - Inga Mekkin Guðmundsdóttir Beck 1988- (2012)
This thesis is an English creative writing thesis and is divided into two parts. The first part is a novella called Working Title about a young English woman named Emily Davies. Emily, known to her friends simply as Em, is going to Iceland for the first time in her life. She suffers from an irrational fear of flying and the only thing she has for comfort on the plane is a book. However, it is a book she does not understand, it is worn and tattered and she has had it in her keeping for years without being able to read it as it is written in a foreign language. The purpose of her trip is to return the mysterious book to its owner. Yet she is not entirely alone, there are other people on the plane. Through a fellow passenger’s bottomless curiosity we learn where Em comes from, discover her past, realise what may be waiting for her in Iceland and wonder why the book carries so much significance in her life. The second part is an exposition of the story and its writing process. It discusses the development of the idea from beginning to end, the progress of the characters’ creation as well as any research that was carried out in connection with the story, its characters and setting. Finally it takes a look at themes appearing in the story and the lessons learned throughout the creative process. Each topic is supported by ideas and examples from published writers and writing instructors as well as literary, cultural and anthropological texts discussing how each one influenced the writer and the story. In short, the exposition describes the wild "tail"-chase that is creative writing.